齿轮系统刚柔耦合动力学建模与仿真研究 - 王炎; 马吉胜; 蒙刚; 谢正军 (Jixie Chuandong, 2009)
The rigid-flexible coupled prototype of gear system which containing flexible shaft and flexible box is established by Virtual.Lab Motion,and the non-linear factors are considered.The loads of main parts are calculated by simulating,and it provides theory for predicting the gear system residual life.By contrasting with the node’s acceleration signals of the test,the possibility of doing faults diagnosis and forecast for gear system with virtual prototype is validated,and so these provides new ways for this field.